Intensitas serangan Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) pada pertanaman jagung di Kabupaten Garut dan Tasikmalaya, Jawa Barat - Wara Asfiya; Vani Nur Oktaviany Subagyo; Anik Budhi Dharmayanthi; Fatimah Fatimah; Rina Rachmatiyah (Jurnal Entomologi Indonesia, 2020)
The presence of Spodoptera frugiperda J.E. Smith or fall armyworm (FAW) have now detected in West Java. However, no information is available on their attack intensity even though the data is crucial for the implementation of appropriate control methods. The investigations were carried out in Garut (Limbangan, Wanaraja, dan Banyuresmi) and Tasikmalaya (Sukaratu) Regencies from 25 to 27 February 2020. At each location, 100 plants were selected for recording observations on leaf damage following the Davis Scale. The results showed the attack intensity in Wanaraja (34,78%), Banyuresmi (34.78%), and Sukaratu (39.89%) showed moderate damage. On the other hand, Limbangan one of the corn production center, showed high damage with the intensity of the pest up to 52.78%. The attack intensity of FAW tends to correlate with their attack level. This means that plant damage levels increasing at higher attack levels.